Web-Monitoring Based Visualization of Virtual Laboratory User Data on Openstack Telemetering Components - Lizadi, Prajaka Brian; Isnianto, Hidayat Nur (Journal of Internet and Software Engineering, 2020)
Currently the use of Cloud computing to meet human necessity was become more common. Cloud computing more comfort provide given because of his model is placed in a container and allows easily accessible according to necessity in various locations. One of the Cloud computing platform that is widely started using are Openstack , because of the ability to manage and regulate the entire system through a web-based dashboard, the command line and through RESTful API. One of the supporting components computing system on a platform Openstack is a project that serves as a Ceilometer telemetering data to present the results of the monitoring, but it is still the raw data that require interface for communication data and human beings. This research created a system of data visualization as an interface to use by admin and users in monitoring data usage per instance on a virtual laboratortium. The result from this research is web monitoring interface with differents graphic type and specification to engage admin requirement for analisys in virtual laboratory activity.